Beyond tissue: Liquid biopsy's promise in unmasking oral cancer - Sakshi Deorah; Akanchha Singh; Shalini Gupta (Oral Oncology Reports)
Oral squamous cell carcinoma (OSCC) is a prevalent malignancy of the oral cavity. It arises from complex interactions between personal lifestyle, genetics, and environmental factors, including tobacco smoking, betel chewing, alcohol consumption, viral infections, and radiation exposure. The high mortality and morbidity rates associated with this disease underscore the need for early detection tools and effective screening strategies.Traditional diagnostic methods, primarily tissue biopsy remain the gold standard for Oral potentially malignant diseases (OPMDs) and OSCC. However, tissue biopsy has limitations such as invasiveness, cost, and inability to capture tumor heterogeneity effectively. To address these challenges, recent research has focused on liquid biopsy, a minimally invasive technique that allows the assessment of tumor-derived components in various biological fluids.A comprehensive search in PubMed, Scopus, and Google Scholar was performed using relevant keywords to structure this review. Only English articles were included and assessed according to titles, abstracts, and full texts. This review delves into blood and salivary biomarkers, including circulating tumor cells (CTCs), cell-free DNA (cfDNA), circulating tumor DNA (ctDNA), exosomes, and microRNA (miRNA), as potential tools for OSCC diagnosis. CtDNA, in particular, represents tumor-derived DNA fragments in the systemic circulation, offering valuable insights into the disease's status. Liquid biopsy, in conjunction with these biomarkers, holds promise as a non-invasive and efficient approach to early OSCC detection, potentially revolutionizing diagnostic methods and improving patient outcomes.